USING INTERACTIVE GAMES AND MOBILE APPLICATIONS IN TEACHING ENGLISH (Ustozlar uchun, 2025)
The integration of interactive games and mobile applications into English language teaching transforms traditional lessons into dynamic, engaging, and learner-centered experiences. These digital tools enhance motivation, enable individualized learning, develop communication skills, and create a meaningful environment where language is acquired naturally through practice and play.